Uso de adoçantes não nutritivos e consumo alimentar de participantes do Estudo Longitudinal de Saúde do Adulto (ELSA-Brasil) - Moreira, Taiz Karla Brunetti (2018)
Nonnutritive sweeteners (ANN) intake has been increasing in the population, regardless of the presence of some morbidity. It’s aimed at reducing the consumption of simple carbohydrates with a view to glycemic control and / or body weight. The effects of ANN use on the food consumption of the population have not been yet fully elucidated and are often inconsistent. The aim of this study was to correlate the association between the regular use of ANN and the diet composition of participants of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Data from ELSABrazil baseline participants (n = 15,105) were used. After exclusion, data from 9,226 participants were analyzed. It was considered regular consumption of ANN its use at least once a day in beverages. Food consumption data were collected with a validated food consumption frequency questionnaire for the study population. The energy content, macronutrients and dietary fiber were estimated. The associations between the exposure variables and the outcome were tested using bivariate tests. Those with p-value <0.05 were inserted into the adjusted models. Multivariate analyzes were performed using crude linear regression models and adjusted for sociodemographic and lifestyle variables previously tested. The analyzes were performed using SPSS software version 23 and the significance level adopted was 5%. The prevalence of regular ANN use was 25.7% (95% CI 24.8 - 26.6), higher in women (30.5%). ANN consumption increased with age as well as with BMI categories. After adjustment, the statistical models showed that regular ANN users consume more fat, total protein, animal and soluble fiber, and lower amounts of energy, total and simple carbohydrate. Thus, regular use of ANN seems to be a more efficient strategy for reducing the consumption of simple carbohydrates than for energy, since it seems to compensate for the consumption of other nutrients.